Jahresbericht des Vereins Kunsthalle Bern 1992 / 93. - Hahnloser, Bernhard; Loock, Ulrich; Kunsthalle Bern (Bern : Kunsthalle Bern, 1993)
Tuymans, Luc ; Schouten, Marien ; Taylor, Al ; Grosvenor, Robert ; Annen, Giro ; Gysi, Peter ; von Niederhäusern, Adrian ; Asher, Michael ; Haagmans, Fons ; etc.
Duits
boek